Design of SRM for Air-conditioned Buck-Boost PFC Converter for Power Quality Improvement - M. Rama Subbamma, Mrs.; V. Madhusudhan, Dr.; P. Sujatha, Dr. (International Journal of Engineering and Technology, 2018)
Now-a-days, in many heavy duty applications Switched Reluctance Motor (SRM) is made as a primary choice having high efficiency and low maintenance. SRM has stator windings but no rotor windings, hence very simple in construction. SRM needs DC supply for its excitation, thus we need to convert the available AC supply to DC by using converters. The converter used for this drive produces very high distortion in the source voltage and current which is not permissible in the system. This paper describes, how to eradicate the disturbance in the input voltage and currents using Â Buck-Boost converter as power factor correction (PFC) converter to improve the power factor. Buck-Boost converter along with delivering required output dc link voltage performs the task of power factor correction (PFC) converter. The design analysis (calculations) of 200V, 2KW, 2500 RPM SRM was described. Basic operation of SRM was detailed along with the asymmetric converter topology. Control circuit of proposed system controls the switching process of converter and correction of power factor was achieved. Analysis of SRM drive for air-conditioner (ac) application with Buck-Boost converter for PFC was carried out in proposed work with various conditions like initial condition, fixed DC voltage, variation in supply voltage. MATLAB/SIMULINK model of SRM drive for different conditions said above were developed and results were also discussed in this paper. Speed and torque characteristics were shown for all the cases. Voltage and current waveforms representing power factor is shown for the SRM drive system with PFC Buck Boost converter. Comparison between Diode bridge rectifier fed SRM and with PWM and BBC fed SRM were given along with their THD. THD was reduced and limited within IEEE standards when operating SRM drive with PFC converter.Â Â